2015
DOI: 10.1002/aic.14894
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthally oscillating membrane emulsification for controlled droplet production

Abstract: A novel membrane emulsification (ME) system is reported consisting of a tubular metal membrane, periodically azimuthally (tangentially) oscillated with frequencies up to 50 Hz and 7 mm displacement in a gently cross flowing continuous phase. A computational fluid dynamics (CFD) analysis showed consistent axial shear at the membrane surface, which became negligible at distances from the membrane surface greater than 0.5 mm. For comparison, CFD analysis of a fully rotating ME system showed local vortices in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Microfabricated pore arrays are similar to massively parallel T junctions, through which one fluid may be introduced into another at an overall much higher flow rate than is possible in individual channels [29]. The mixing rate can 4 be enhanced by providing a controlled shear at the membrane surface using cross flow [30], stirring [23], flow pulsations [31], radially or axially oscillating membrane tube [32,33], and rotating membrane [24]. However, the role of different pore arrangements, pore shapes and fabrication methods on the performance of microfabricated membrane in micromixing process…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Microfabricated pore arrays are similar to massively parallel T junctions, through which one fluid may be introduced into another at an overall much higher flow rate than is possible in individual channels [29]. The mixing rate can 4 be enhanced by providing a controlled shear at the membrane surface using cross flow [30], stirring [23], flow pulsations [31], radially or axially oscillating membrane tube [32,33], and rotating membrane [24]. However, the role of different pore arrangements, pore shapes and fabrication methods on the performance of microfabricated membrane in micromixing process…”
Section: Graphical Abstractmentioning
confidence: 99%
“…In an oscillating ME system, tubular membrane can oscillate tangentially clockwise and counter-clockwise (Silva et al 2015) or radially upward and downward (Holdich et al, 2010), with frequencies from 10 to 90 Hz.…”
Section: Emulsification Using Microengineered Membranesmentioning
confidence: 99%
“…cross-flow), shear stress is uniformly distributed over the membrane surface and localised to the membrane wall rather than the entire bulk volume of the fluid. A Computational Fluid Dynamics (CFD) analysis has shown that in an azimuthally oscillating membrane emulsification system, shear rate becomes negligible at radial distances from the membrane surface of just 0.5 mm although the shear rate could be 1400 s −1 at the membrane surface (Silva et al, 2015). Due to controlled localised shear and geometrically-mediated drop formation, the droplet size can be precisely controlled over a wide range and a narrow droplet size distribution can be achieved.…”
mentioning
confidence: 99%
“…Previously in [1] a novel membrane emulsification device was presented which operates continuously. In [1] a throughput of 1 L h -1 was tested using a 5 µm pore size membrane with an interpore distance of 200 µm.…”
Section: Introductionmentioning
confidence: 99%
“…In [1] a throughput of 1 L h -1 was tested using a 5 µm pore size membrane with an interpore distance of 200 µm. Droplets generated at some conditions were below 50 µm which suggests decreasing the interpore distance by at least three times will still avoid the contact of drops during their growth and detachment.…”
Section: Introductionmentioning
confidence: 99%